Avaliação de políticas públicas: estudo do comportamento de indicadores relacionados com a saúde em municípios do estado de Pernambuco após a emenda Constitucional Nº 29 - Silva, André Ricardo Batista de Barros e (2008)
The Brazilian Public Health System (Sistema Único de Saúde - SUS), defined by the Constitution of 1988, is almost 20 years old and is a landmark for health public policies. In these 20 years, the law was altered several times with the objective of prioritizing the investment of public money in such a needy area as health. Among these changes, it is important to single out the Constitutional Amendment number 29, issued on 13th September 2000, which determined the minimum investment in health. According to this amendment, as from the year 2000, the municipalities should invest in health services a minimum of 7% of the revenue from taxes and transferences from the Federal and State governments. This value was to rise gradually to 15% by 2004. Since every public policy should be systematically evaluated and considering the assumption that, according to the incrementalist theory, more money invested in health would tend to solve the crisis in the health system, this dissertation consists of a study of a set of health indicators in some municipalities of the State of Pernambuco after the Amendment 29. The evaluation period spanned 4 years, from 2002 to 2005 and the area chosen for the study was located in southern agreste region of the state. Ten health indicators were selected, all of which included in the Administrative Rule no 493, of the Health Ministry. It was found that in the chosen period the average investment in health was greater than 15% of the municipalities¿ revenue since 2002. However, the value of the investment per capita, considering the municipality's share of it, which was half of the total investment, decreased from 2002 to 2004 and increased in 2005. It was also found that the municipalities with the lowest per capita income were the ones with the highest investment per capita in health. As regards children mortality in the region, it was on average 33 for every 1000 children born, which is classified as ¿medium¿ according to the above mentioned Administrative Rule no 493. No statistically significative correlation was found between the amount of money invested in health and children mortality.